IBNU THUFAIL SEBAGAI MODEL PERADABAN ISLAM - Mubarak, Ahmad Zaki (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
This paper studies one of the ntayor of muslinr philosophy tlrat's lbn Thulail, known as Abu Bacer in Latin t-anguagc. According to thc writcr, the illurnination thought of Ibn Thul-ail lourrd on the story of' I-layy iltn Yuq:hun at lcast also an exantple ot- knowlcdge thcory. l-hc illuntinalion thoght ol'lbnLr T'hufail was his combination and interection with thc philosophy tradtion in that timc, tlrat tlrc plrilosophical tlrougltt of'Aviccnna. So, it's unclcrstaltd fiorn thc statement of Ibnu T'huail lris sclf that his illunrination thouglrt lound ilr thc story of Ilqtlt illp Yaqzhan is thc explanation ol thc sccrcct of oticntcl plr i losolllry ol' Av iccttttc.",